Contemporary journalism as part of a communicative resource. (Herald of Journalism, 2016)
The article examines the contemporary journalism as part of a communicative resource. Component in a journalistic articles, interviews Fridman T., A. Rotfeld, J. Fischer as the unifying theme of the essence of people a globalized world.
Keywords: Humanities; intellectual discourse; communication; journalistic component journalism.